Pengaruh Profitabilitas dan Kebijakan Dividen Terhadap Nilai Perusahaan Dengan Struktur Modal Sebagai Variabel Mediasi - Muslichah; Oniber Subana Hauteas (Jurnal Manajemen dan Keuangan, 2019)
This study aims to analyze the direct and indirect effect of profitability and dividend policy on the value of the company. Objects in this research are companies incorporated in LQ 45 in the period of 2015-2017. Samples are taken using purposive sampling method. Data of this study was analyzed using path analysis. The results of the study show four important findings: (1) the effect of profitability on firm value is positive and significant, (2) the direct effect of dividend policy on firm value is not significant, (3) the effect of profitability and dividend policy on capital structure is positive and significant (4) capital structure mediates the effect of profitability and dividend policy on firm value